Persepsi Siswa Tentang Kompetensi Guru dan Konsistensi Akhlak di Media Sosial pada Madrasah Aliyah (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to examine students’ perceptions of teachers’ competence in fostering students’ self-efficacy to validate religious information on social media, as well as to explain how students at State Senior High Schools maintain consistency in their affective (moral) learning outcomes amidst a flood of contradictory digital content. This research employs a qualitative literature review method, analysing scientific articles, books, and research reports relevant to teacher competence, self-efficacy, digital literacy, and moral education. The findings indicate that students’ positive perceptions of teachers’ academic, pedagogical, and personal competencies contribute significantly to the development of students’ self-efficacy in validating religious information encountered on social media. Teachers are positioned as the primary point of reference when students encounter questionable information, thereby helping to prevent exposure to hoaxes and misleading content. Furthermore, the internalisation of moral values through learning, teachers’ exemplary behaviour, the practice of religious rituals, and extracurricular activities forms a strong affective foundation. This foundation enables students to maintain consistent moral behaviour in the digital space. These findings underscore the importance of strengthening teachers’ competencies and developing contextually relevant digital literacy programmes in madrasahs.